Long‐Range Exciton Migration in Coassemblies: Achieving High Photostability without Disrupting the Electron Donation of Fluorene Oligomers. (1st February 2021) - Cheng, Chuanqin; Gong, Yanjun; Guo, Yongxian; Cui, Linfeng; Ji, Hongwei; Yuan, Hong; Jiang, Lang; Zhao, Jincai; Che, Yanke
Abstract: In this work, photostable coassemblies from a nonphotostable fluorene oligomer (the energy donor) and a photostable oligomer (the energy acceptor) are fabricated. Long‐range exciton migration over a net distance of about 370 energy‐donor molecules to energy acceptors is demonstrated in such coassemblies. The fast and long energy migration allows harvesting of the excitation energy of energy donors by embedding a small number of energy acceptors for photostability enhancement. Importantly, embedding a small number of energy acceptors in coassemblies causes a negligible negative influence on the electron donation of energy donors that are desired in practical applications. The advantages of the coassemblies fabricated, that is, high photostability without disrupting the electron donation of energy donors, are well illustrated in fluorescence detection of trace explosives where prolonged working life and improved detection capacity are achieved. Abstract : Long‐range exciton migration in coassembled superstructural microspheres (SMS) leads to embedding a small number of energy acceptors to afford efficient energy communication with energy donors, which not only creates high photostability but also preserves the properties of energy donors. The advantages of the coassembled SMS are illustrated in the sensitive fluorescence detection of trace explosives.